Análisis comparativo de la evolución de los bonos verdes en América latina - Vinueza Ruiz, Luis Ángel (2025)
This research analyzes the growth and evolution of the green bond market in Latin America, focusing on its use as a financial tool to mitigate climate change and promote economic sustainability. The study aims to assess the current state of green bond markets, the effectiveness of public policies, and the fiscal incentives that have facilitated their adoption in key countries such as Chile, Brazil, and Mexico, which have led green bond issuances for several years and possess the most robust legislation in the region. Using a descriptive and documentary research methodology with a qualitative approach, the study incorporates information from international organizations such as the IDB, IMF, ICMA, and ECLAC, as well as regional economic data and case studies from companies like Colbún, Petrobras, and Coca-Cola FEMSA, among others. The findings indicate that by 2023, the total issuance of green bonds in Latin America reached USD 31.145 billion, with Chile, Brazil, and Mexico leading the market. Chile consolidated its position as the region's largest issuer, with USD 17.306 billion, supported by a strong regulatory framework including the Framework Law on Climate Change. Brazil, leveraging its Green Protocol established in 1995, issued USD 12.131 billion, while Mexico accumulated USD 5.586 billion, significantly advancing through the implementation of a sustainable taxonomy and the Green Bond Principles MX. The analysis of regulatory policies, financing mechanisms, and regional projects identified the factors driving or hindering market development. To attract greater investments, the conclusions emphasize the need to harmonize regional standards, accelerate the implementation of regulatory frameworks, and promote international cooperation. This study provides key evidence on how financial markets can support sustainable development goals, positioning Latin America as a leader in sustainable finance and the transition to a low-carbon economy. It highlights not only the environmental impact of green bonds but also their potential to foster social equity and economic resilience.